Model Penilaian Sharpe Ratio Untuk Peningkatan Kinerja Reksa Dana - Rini Nur Indah Lestari; Muhammad Fachrudin Arrozi (Jurnal Akuntansi dan Keuangan, 2023)
This study seeks to determine the impact of Inflation, Operating Costs, and Mutual Fund Size on Mutual Fund Performance either concurrently or in part. In this research, The Sharpe approach was used to gauge the mutual fund dependant variable. The focus of this study is a conventional and sharia-compliant stock mutual fund that is registered with the Financial Services Authority. Purposive sampling is the technique employed.. The sampling technique used was 38 equity mutual funds with a research period of 2017 – 2021. Secondary data are the sort of data used in this study. This research uses the Multiple Linear Analysis method. The results showed that simultaneously Inflation (INF), Operating Cost (OC) and Mutual Fund Size (SZ) had a profound impact on Mutual Fund Performance. Inflation (INF) does not significantly affect the performance of mutual funds. Meanwhile, Operating Costs (OC) and Mutual Fund Size (SZ) partially have a big impact on mutual fund performance.